Optimizing Hajj Fund Investments Through Valuation Analysis Of Sharia-Compliant Stocks - Saputro, Diky; Qadri, Resi Ariyasa (Journal of Law, Administration, and Social Science, 2024)
This investigation endeavors to dissect stock valuation methodologies within the consumer goods sector listed on the Jakarta Islamic Index (JII70), aiming to establish a foundational basis for investment decision-making aligned with Sharia principles, particularly for the Hajj Financial Management Agency (BPKH), which administers the Hajj fund. The empirical data underpinning this analysis comprise the financial statements of the companies under scrutiny. Secondary data, essential for this study, are sourced from publications disclosed on the official websites of the respective companies. The selection of sample companies employs a purposive sampling technique, focusing on entities characterized by robust market liquidity and a consistent history of dividend distribution. The valuation techniques applied in this study include the price multiple (P/E and P/B ratios) and the dividend discount model. The findings of this research reveal that PT Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO) is undervalued, exhibiting a potential discrepancy of 15% between its market price and intrinsic value. This study aspires to serve as a seminal reference for subsequent inquiries into stock valuation within the domain of Islamic finance, enriching the academic and practical understanding of Sharia-compliant investment strategies.